Competition performance of the Croatian wrestling team at major competitions - Slacanac, K.; Pekas, D.; Žugaj, N.; Škugor, K.; Curic, M. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Monitoring of competitive performance in wrestling over the years has evolved, and the results of analyses are publicly available immediately after the competition. Analyses of major wrestling competitions provide wrestlers and coaches with feedback on competitive e ciency and allow for better technical-tactical preparation of wrestlers. To improve the competitive e ciency of Croatian wrestlers in major wrestling competitions, an analysis was conducted to determine the structure of o ensive and defensive activities. The analysis of the di erences in won and lost points by Croatian Greco-Roman wrestlers in the major wrestling competitions in the Olympic cycle 2020-2024 shows that they signi cantly won points using passivity (22,0%) and gut wrench techniques (38,6%), while they lose the most points using techniques such as take down (12,4%), hip turning throw (5,9%), forward bending throw (7,6%), and lifts (22,4%). The results of this study indicate a de cit in the defensive phase in the parterre position and very weak o ensive e ciency compared to the modal characteristics of medalists in major wrestling competitions. Further analysis of tactical preparations, biomechanical and conditioning readiness analysis for each wrestler, analysis of implemented training programs (number of days, sparring partners, training duration), and timing of Croatian wrestlers' form is necessary. The limitation of refers to use of di erent names of variables as well as use di erent set of variables in other studies, because of that it is necessary to standardize and precisely describe variables to be appropriate, understandable and applicate to next researches.